2012
DOI: 10.1152/japplphysiol.01275.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical effect of rat flexor carpi ulnaris muscle after tendon transfer: does it generate a wrist extension moment?

Abstract: Maas H, Huijing PA. Mechanical effect of rat flexor carpi ulnaris muscle after tendon transfer: does it generate a wrist extension moment?. J Appl Physiol 112: [607][608][609][610][611][612][613][614] 2012. First published December 1, 2011; doi:10.1152/japplphysiol.01275.2011.-The mechanical effect of a muscle following agonist-to-antagonist tendon transfers does not always meet the surgeon's expectations. We tested the hypothesis that after flexor carpi ulnaris (FCU) to extensor carpi radialis (ECR) tendon tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…In fact, it has been reported that changes in connective tissue layers between synergistic muscles are not equally expressed in passive and active states (Smeulders et al. 2002; Maas and Huijing 2012a; Bernabei et al. 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that changes in connective tissue layers between synergistic muscles are not equally expressed in passive and active states (Smeulders et al. 2002; Maas and Huijing 2012a; Bernabei et al. 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our observed relative displacements and the previously reported minimal mechanical interaction between submaximally activated muscles suggest that during level and upslope trotting, the extent of epimuscular force transmission between ankle plantar-flexors is not significant in healthy rats. This may change in pathological conditions of the musculoskeletal system, such as those caused by muscle injury and surgical interventions, for which enhanced mechanical interactions between muscles have been reported (Bernabei et al, 2016a;Maas and Huijing, 2012).…”
Section: Mechanical Consequences Of Displacements Between Neighboringmentioning
confidence: 99%
“…The palmar side of the right hand was tied to a small aluminum plate with 1–0 silk sutures. The right forelimb was secured rigidly to our custom-built apparatus to assess isometric wrist joint moments in the rat (Figure 1D, see also 26). The apparatus consists of a hand fixation unit, which is connected to a force transducer (Hottinger Baldwin, maximal output error <0.1%, compliance of 0.0048mmN -1 ) mounted on a single axis micropositioner.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly relevant, because scar tissue formation, frequently observed following invasive orthopedic surgeries [22,23], is reported to affect the mechanics of transferred as well as of neighboring muscles considerably [24–26]. In addition, several studies in human patients, as well as various animal models (e.g., rats, cats and monkeys) have shown that neural adjustments of motor patterns occur only partially, or do not occur at all [2731].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation